Developing a Comprehensive Social Security System in Uzbekistan: Challenges and Opportunities (European Journal of Economics, Finance and Business Development, 2023)
This research paper aims to explore the challenges and opportunities in developing a comprehensive social security system in Uzbekistan. It examines the current state of social security programs in the country, identifies the key obstacles to achieving an integrated system, and highlights potential opportunities for improvement. The paper also discusses the importance of a comprehensive social security system in reducing poverty, addressing vulnerabilities, and promoting inclusive development. By analyzing the existing gaps and proposing potential solutions, this research paper provides insights and recommendations for policymakers and stakeholders in Uzbekistan's social security sector.